Modeling academic satisfaction based on the six factors of Hexaco personality with the mediation of motivation to progress in students of Islamic Azad University, Roudhen branch - Tania Taheri; Nastaran Sharifi; Malek Mirhashemi (مجله علوم روانشناختی)
Background: Existing literature in this domain reveals a gap in research, as no study has been conducted to model the satisfaction of university students at the Islamic Azad University based on the six-factor personality model, HEXACO, with motivation for progress as a potential mediator. This underscores the need for an investigation into the interplay between personality factors, academic satisfaction, and the motivating forces for academic advancement among students at the Islamic Azad University. Aims: The present study was conducted with the aim of modeling academic satisfaction based on the six factors of Hexaco personality with the mediation of motivation to progress in the students of Islamic Azad University, Roudhen Branch. Methods: The research method was correlational. The population of this study was the students of Islamic Azad University, Roudhan branch, in the academic year of 1402-1401. 315 people were selected using random sampling method. The data collection tools were the Hermans achievement motivation test (1970), the students' academic satisfaction scale (Terekzadeh and Mesbeh, 2013) and the 60-question Hexaco scale (Ashton and Lee, 2009). Results: Data analysis using the structural equation modeling approach showed that the academic satisfaction model has a favorable fit based on the six factors of Hexaco's personality with the mediation of students' progress motivation. The effect of Hexaco's personality trait dimensions on academic satisfaction is significant (P< 0.0005); So that honesty, humility, β= 0.341, openness to experience, β= 0.426, conscientiousness, β=0.513, extroversion, β=0.363, adaptability, β= 0.420, and excitability, β= 0.392, were reported.. Also, achievement motivation has an effect on academic relationship satisfaction (β= 784; P< 0.0005). Conclusion: It seems that studying the level of satisfaction with education and academic motivation of students can be an indicator for improving academic performance. Also, it seems that the psychological and personality evaluation of the applicants to enter the universities can lead to the selection of a suitable field of study and create higher academic satisfaction.